PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATIONS (TAI) UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SAINS BIOLOGI SISWA KELAS VIIA SMPN 4 KUNTO DARUSSALAM KABUPATEN ROKAN HULU TAHUN AJARAN 2011/2012 - Wan Syafi’i; Rosmaini S; Rofika Setyari (Program Studi Pendidikan Biologi, 2012)
This study aims to improve motivation and learning outcomes with the application of biological science cooperative learning model Team Assisted Individualizations (TAI) in a class VIIa SMPN 4 Kunto Darussalam FY 2011/2012. The research was conducted in January-February 2012. Subjects were students in grade 4 Kunto Darussalam VIIa SMP totaling 34 students consisting of 17 students and 17 students. Parameters is motivated by categories: challenge, curiosity, participation, and control, learning outcomes consisting of absorption, the thoroughness of learning and group awards, student activities and teacher activities. The average student motivation prior to the application of learning models, namely TAI 53.12% (average) increased after the application of learning models with an average TAI is 83.00% (high) and the absorption of students in the cycle I is 83.53% (both ) increased in the second cycle to 85.74% (good). Thoroughness of student learning in the cycle I is 70.59% and in the second cycle increased to 94.12%. I cycle a group award for the award and a great group of super 2 4 groups. In the second cycle there are two groups of super honored, three groups received a great award, and one group received both awards. Student activity in the cycle I is 66.24% (or less) increased in the second cycle is 75.75% (enough). I cycle activity with the teacher on an average of 100% (very good) as well as in the second cycle is 100% (very good). From the results of the study concluded that the application of cooperative learning model TAI can increase the motivation to learn science and biology students in grade 4 Kunto Darussalam VIIa SMP Rokan Hulu FY 2011/2012.Keywords: Cooperative Study Team Assisted Individualizations (TAI), Learning Outcomes, Motivation,